Love Attitudes and Violence: Consequences of Burden of Care on Women - Marisol Díaz; Ana Estévez; Janire Momeñe; Nagore Ozerinjauregi (Clínica y Salud. Investigación Empírica en Psicología, 2019)

(untitled)
Intimate partner violence against women is considered one of the most widespread forms of violence. Women staying in violent relationships is associated with feelings of love and caregiving. The objectives of this study were to investigate potential associations between violence (received and perpetrated), love styles, and perceived caregiver burden; to assess differences in the type of violence as a function of perceived caregiver burden; to analyse the predictive role of violence received and perpetrated and love styles in caregivers’ burden; and to determine whether love styles mediate in the relation between violence and perceived caregivers’ burden. Two hundred fifty women from the Basque Country(Spain), aged between 30 and 84 years (M = 58.66, SD = 10.46) participated in the study. It is a transversal study design. Results show a positive correlation between low burden and psychological aggression perpetrated. Further, the Agape love style and severe and minor psychological aggression perpetrated, and minor injury perpetrated were predictors of perceived caregiving burden. Finally, the findings indicate that love styles mediate the relationship between violence and care burden. The study concludes that love styles and perpetrated and received violence influence women’s perceived caregiver burden. This should be taken into account when evaluating relationships.